Analysing the Hate Speech Within the Framework of Political Discourse - Stevanović, Aleksandar (Zbornik Instituta za kriminološka i sociološka istraživanja, 2023)
The author considers hate speech within the broader context of the right to freedom of expression with specific reference to political speech. The European Court of Human Rights, in its jurisprudence, takes the stance that the protections for freedom of expression extend to content that might be offensive, shocking, and disturbing to someone. It is also well accepted in comparative case law and doctrine that political speech has a privileged position in terms of legal protection when it comes to a greater degree of criticism. On the other hand, it is extremely important to protect individuals and collectives from exposure to hate speech since it does not achieve the objectives of the right to freedom of expression in any way. However, it is clear at first glance that in a large number of cases, there is an intertwining of hate speech with speech to which the law provides legal protection. Content related to racial, negationism, revisionism, religious, ethnic, etc. issues is a legitimate and integral part of political discourse, while a very small space separates them from slipping into the field of hate speech. Although the historical, cultural, sociological, and psychological context is important for the qualification of certain content as hate speech, the author seeks to analyze the basics of the definition of hate speech through a comparative legal approach (UN and other international and regional organizations) to offer a framework for distinguishing hate speech from other permitted content which would be applicable in general, appreciating all the possible variables that affect the qualification of hate speech.